A Universidade do Porto e a vida nacional : cronologia sinóptica (1911-2010) - Homem, Armando Luís de Carvalho (2011)
Synoptic chronology of the University of Porto, in time of its Centennial, and of its faculties and of the social and political projection of some scholars.